Improving flexibility and dependability of remote patient monitoring with agent-oriented approaches. (2018) - Ancona, Davide; Ferrando, Angelo; Mascardi, Viviana
Remote patient monitoring (RPM) enables physicians to perform diagnosis and treatment remotely through sensors connected via a communication network. Dependability and flexibility are recognised as two key technological requirements for RPM take off. In this paper we address the questions of how RPM systems designed and implemented as multiagent systems (MASs) can ensure flexibility and dependability, and which agent-oriented approach is more suitable to achieve this goal. We analysed five state-of-the-art agent-oriented approaches according to ten features. Since no approach among the five clearly dominates the others, we selected the one we are more familiar with, parametric trace expressions. We used them to verify properties modelling existing medical guidelines and to develop a prototype where newborns suffering from hypoglycemia must be continuously monitored, showing how agentoriented approaches in general, and parametric trace expressions in particular, are suitable for engineering flexible and dependable RPM systems.